2014
DOI: 10.1155/2014/286914
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of Hepatitis A Infection with Extrahepatic Manifestations

Abstract: Hepatitis A has a variety of associated extrahepatic manifestations that clinicians should be aware of for early diagnosis and treatment. We report a unique case of hepatitis A presenting with multiple extrahepatic manifestations not previously described in a single patient. A 34-year-old male presented with sudden onset of left sided facial pain, swelling, and skin rash, with diffuse body pains and muscle weakness, and was found to be positive for hepatitis A immunoglobulin M (IgM). He was initially started o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…noted that direct invasion of HAV into the kidney tissues as well as immune-related mechanisms may lead to ARF. (11) In our literature review, previous reports of ophthalmic manifestations associated with HAV infection were not found. Stangos et al reported a case of multiple evanescent white dot syndrome (an in ammatory chorioretinal disorder) 10 days after receiving simultaneous formalin-inactivated HAV and live-attenuated yellow fever vaccine.…”
Section: Case Reportmentioning
confidence: 67%
See 2 more Smart Citations
“…noted that direct invasion of HAV into the kidney tissues as well as immune-related mechanisms may lead to ARF. (11) In our literature review, previous reports of ophthalmic manifestations associated with HAV infection were not found. Stangos et al reported a case of multiple evanescent white dot syndrome (an in ammatory chorioretinal disorder) 10 days after receiving simultaneous formalin-inactivated HAV and live-attenuated yellow fever vaccine.…”
Section: Case Reportmentioning
confidence: 67%
“…Bhatt at el. reported a 34 year-old man with acute parotitis and facial skin rash as the manifestations of HAV infection 6 days prior to any hepatic presentations (11) These ndings suggest that extra-hepatic manifestations of HAV infection may occur before (during incubation period) or after the presentation of systemic and hepatic signs secondary to deposition of circulating immune-complex in various organs.…”
Section: Case Reportmentioning
confidence: 86%
See 1 more Smart Citation
“…Extrahepatic involvement is rare unlike in hepatitis B or hepatitis C infection. 2 Extrahepatic manifestations may include acute kidney injury due to immune complex glomerulonephritis, 2 urticarial and maculopapular rash, polymyositis, arthralgias, suppurative parotitis, 3,4 acute pancreatitis, acute cholecystitis, and bone marrow suppression leading to cytopenias, which can be seen in both the prodrome phase and acute infection. 1,2 Hepatitis A virus (HAV) rarely involves the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…2 Extrahepatic manifestations may include acute kidney injury due to immune complex glomerulonephritis, 2 urticarial and maculopapular rash, polymyositis, arthralgias, suppurative parotitis, 3,4 acute pancreatitis, acute cholecystitis, and bone marrow suppression leading to cytopenias, which can be seen in both the prodrome phase and acute infection. 1,2 Hepatitis A virus (HAV) rarely involves the central nervous system. 4 Hemophagocytic lymphohistiocytosis (HLH) is a disorder of uncontrolled, pathological activation of the immune system leading to extreme hyperinflammation.…”
Section: Introductionmentioning
confidence: 99%